2019
DOI: 10.1093/geroni/igy039
|View full text |Cite
|
Sign up to set email alerts
|

Digital Pathways to Positive Health Perceptions: Does Age Moderate the Relationship Between Medical Satisfaction and Positive Health Perceptions Among Middle-Aged and Older Internet Users?

Abstract: ObjectivesWe explored the influence of e-trust, e-health literacy, e-health information seeking, and e-health information consumerism on medical satisfaction and positive health perceptions.MethodsOur sample consisted of 499 randomly selected panel members aged 40–93. We employed hierarchical ordinary least squares (OLS) regression analyses and structural equation modeling (SEM). We examined the moderating role of age on the relationship between medical satisfaction and positive health perceptions.ResultsA sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 66 publications
1
19
0
1
Order By: Relevance
“…Nonadherence with medical professionals was not a significant predictor of patient-reported outcomes. As Seckin et al [ 51 ] noted, prior to the 1980s, the passive patient was expected to accede to their physician’s authority by conforming to their physician’s stipulated treatment and advice. Socialization of older cohorts into medical paternalism, which promoted a doctor knows best approach for health care increased the tendency of older adults to show compliance with medical professional authority, which offers a potential explanation for this specific nonsignificant association in the older sample [ 1 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonadherence with medical professionals was not a significant predictor of patient-reported outcomes. As Seckin et al [ 51 ] noted, prior to the 1980s, the passive patient was expected to accede to their physician’s authority by conforming to their physician’s stipulated treatment and advice. Socialization of older cohorts into medical paternalism, which promoted a doctor knows best approach for health care increased the tendency of older adults to show compliance with medical professional authority, which offers a potential explanation for this specific nonsignificant association in the older sample [ 1 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Internet use for health-related information is also associated with challenges in the doctor-patient relationship, when a health consumer believes that online information is as good as information provided by their provider [ 43 , 48 - 50 ]. Researchers found that trust in information sources affect patients’ attitudes and behaviors, and their satisfaction with interactional and communicational aspects of the clinical encounters [ 51 ]. Medical directives may come from providers, but health consumers’ choices are influenced by a wide range of alternative sources of information on the internet [ 24 , 48 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another significant point related to healthy longevity was the fact that the older population with cognitive and functionally independent abilities acquire healthy behaviors throughout life 2,24,26,29 and can even enjoy digital technology in health management 30 . Such statement reiterates the findings of this research, in which the interviewees considered robust showed a higher prevalence of walking habits, as well as absence of cognitive impairment or depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Disinformation and misinformation online as public concerning issues have been raised [10,11]. eHealth literacy, de ned as "the ability to select, appraise, and utilize good quality health information from the Internet", is of great important to motivate health information seeking and scanning behaviors, evaluate health information, and maximize the potential bene ts of eHealth for their health-related lifestyle [12][13][14][15][16]. Moreover, it had reported that limited eHealth literacy was an obstacle for online health information-seeking behaviors in patients with chronic diseases [17].…”
Section: Introductionmentioning
confidence: 99%